(untitled) (Comprehensive Journal of Science, 2026)
This study sheds light on the impact of the scholarly efforts of the Libyan historian Muhammad al-Wafi in several local and French newspapers. These efforts include a book in French, originally a doctoral dissertation in philosophy, and translations from French into Arabic of historical books on the Islamic and modern history of Libya. Al-Wafi’s interest stemmed from the importance of these sources in documenting historical facts. When a people’s history is written by an author from a foreign country, which differs in ethnicity, religion, and language, the information presented requires careful scrutiny and verification by those translating it into the original language.